Journalists in Film - Heroes , Villains (Edinburgh University Press, 2009)
I have been researching, teaching and writing about journalism for more than two decades. I have also written some 200 pieces of journalism of my own – mainly feature articles, travel pieces and commentary columns for the print and online media.1 Throughout that time I have been fascinated by feature films in which journalism is the subject, or is a central element of the narrative. In my teaching and research work I have found movies a useful, engaging, sometimes inspirational source of knowledge about how, as members of liberal democratic societies in which journalism is highly valued, we view journalists. More often than not they are highly relevant to the analysis and understanding of contemporary debates around news and other forms of journalism. And debates there always are, heated and high on the public agenda, about journalistic ethics, political bias, the effects of commercialisation and competition on the content and style of journalism, structures of ownership and control of news media, the consequences of new communication technologies, the relationship between news media and politics, the role of the journalist in time of war. The films which have been made about journalism are a fruitful pathway into those debates, with the advantage in terms of grabbing students’ attention that they often involve texts which are familiar, even to a non-specialist audience. Mention of Jurgen Habermas’ theory of the public sphere will not always prompt excitement in the lecture theatre. Talking about Richard Gere’s roguish columnist in Runaway Bride (Gary Marshall, 1999)2 will at least get an audience’s attention. This book, necessarily and perhaps fortuitously, makes frequent reference to George Clooney, Angelina Jolie, Kate Winslet, Will Ferrell, and a host of other A-list stars who have made films about journalism and journalists a significant part of their portfolio